Effect of thermal treatment variables on the thermogravimetric properties of eucalypt wood - Nava Soratto, Déborah; Simões da Silva, Carlos Miguel; Rocha Vital, Benedito; Oliveira Carneiro, Angélica de Cássia; Jerásio Bianche, Juliana; Neto Boschetti, Walter Torezani Neto Boschetti; Pereira Freitas, Thaís; Ceccato Ferreira, Juliana (Maderas. Ciencia y Tecnología, 2020)
Thermal treatments have the effect of reducing the hygroscopicity and improving the resistance to microbiological attack of wood by the degradation of its chemical constituents. During the treatments, the mass of the wood is reduced, a factor that can affect the quality of the materials according to their use. The objective was to verify the effect of the thermal treatment variables on the thermogravimetric properties and the chemical composition of Eucalyptus grandis. The treatments were carried out in a vacuum oven with three atmosphere conditions - vacuum; N2; vacuum+N2 at temperatures of 140, 180 and 220 °C for 6 hours. It was observed that the mass loss during treatments differed only according to the temperatures used. The extractive content, total lignin and holocellulose presented significant changes only at 220°C in all three atmospheres. In the thermogravimetric analysis, the greatest value of residual mass was found in the treatment that used nitrogen and 220 °C, thus demonstrating that this treatment was more invasive, leading to the conclusion that the vacuum application can help to reduce the degradation of the constituents of the eucalypti wood. wood, which can lead to the production of thermally treated wood without great losses in the mechanical properties.